2020
DOI: 10.3390/foods9091320
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phenolics and Antioxidant Capacity of Some Wild Edible Greens as Affected by Different Cooking Treatments

Abstract: The study aimed to assess the influence of three cooking methods (boiling, steaming, and microwave-cooking) on (i) composition in individual phenolic compounds, (ii) total phenolic content (TPC), and (iii) total antioxidant activity (TAA) of eight Mediterranean wild edible species (Asparagus acutifolius, Asphodeline lutea, Beta vulgaris, Helminthotheca echioides, Sonchus oleraceus, Taraxacum officinale, Urospermum picroides, Urtica dioica). In raw greens, several caffeic acid derivatives (chicoric, caftaric, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 49 publications
(114 reference statements)
9
35
0
Order By: Relevance
“…Compound 19 was identified as isorhamnetin-rutinoside with an [M − H] − ion at m/z 623 and a characteristic product ion at m/z 315 corresponding to isorhamnetin aglycone and a loss of 308 Da (rutinose). This compound is commonly extracted from marigold for medicinal purposes ( Calendula officinalis L.) [ 53 ] but is also found in other vegetables such as Asparagus acutifolius [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 19 was identified as isorhamnetin-rutinoside with an [M − H] − ion at m/z 623 and a characteristic product ion at m/z 315 corresponding to isorhamnetin aglycone and a loss of 308 Da (rutinose). This compound is commonly extracted from marigold for medicinal purposes ( Calendula officinalis L.) [ 53 ] but is also found in other vegetables such as Asparagus acutifolius [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical compounds such as phenolics are some of the contributors to these health benefits [ 1 ]. When studying the potential health benefits of foods, including vegetables, it is important to evaluate not only the composition of raw food, but also that of cooked foods, including complex food dishes [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, variations in the cooking conditions, such as maximum temperature reached, cooking time, pH, surface/volume relation, water used, oxygen and light presence, matrix and/or food type, as well as compounds sensitivity to these factors can influence the final composition [26,27]. Some research works have been conducted on the analysis of nutritional and phytochemical composition, as well as antioxidant activity of traditionally consumed wild edible plants all over the world [28][29][30][31][32][33][34][35][36][37][38]. For example, Trichopoulou et al [28] reported data of the nutritional composition of Cretan pies elaborated with cultivated and wild vegetables (such as Rumex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Prasanna et al [35], reported the cooking effect (boiling, steaming, and frying) on polyphenols, flavonoids, carotenoids and antioxidant activity of leaves of six edible plants locally collected in Sri Lanka. Sergio et al [38] studied bioactive phenolics and antioxidant capacity of some wild edible Mediterranean greens affected by boiling, steaming and microwave-cooking treatments.…”
Section: Introductionmentioning
confidence: 99%